2016
DOI: 10.1186/s12891-016-1093-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind sham-controlled trial on the efficacy of arthroscopic tennis elbow release for the management of chronic lateral epicondylitis

Abstract: BackgroundTennis elbow is a common elbow pathology typically affecting middle-aged individuals that can lead to significant disability. Most cases resolve within 2 years of symptom onset, but a subset of patients will develop persistent symptoms despite appropriate conservative management. There are several surgical approaches used to treat chronic tennis elbow, with arthroscopic surgery becoming an increasingly popular approach to address this pathology in North America. This procedure involves the arthroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 32 publications
0
26
0
3
Order By: Relevance
“…Elbow arthroscopy, besides being a less invasive procedure preserves the integrity of the skin and underlying tissues, causes less inflammatory reaction, and allows assessing the joint in its entirety for inspecting and ruling out associated pathologies. Many authors [1,6] have described good results with early reintegration to the daily activity after the arthroscopic treatment of the tennis elbow. Miyazaki et al [7] reported results of 20 patients operated over a period of 8 years, obtaining 65% excellent results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Elbow arthroscopy, besides being a less invasive procedure preserves the integrity of the skin and underlying tissues, causes less inflammatory reaction, and allows assessing the joint in its entirety for inspecting and ruling out associated pathologies. Many authors [1,6] have described good results with early reintegration to the daily activity after the arthroscopic treatment of the tennis elbow. Miyazaki et al [7] reported results of 20 patients operated over a period of 8 years, obtaining 65% excellent results.…”
Section: Discussionmentioning
confidence: 99%
“…It has an incidence of 4-7 per 1000 inhabitants per year. Recent studies highlight that between 1-3% of the population will suffer discomfort during the course of life [1]. It affects individuals between 35 and 50 years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most common elbow pathology is the tennis elbow or lateral epicondylitis that commonly affects middle-aged individuals and can cause major discomfort and disability. 1 This condition usually affects persons between 35 and 50 years old and 1-3% of the population may complain of lateral side elbow pain throughout their lifetime. The recorded incidence of tennis elbow is 4-7 per 1000 per year.…”
Section: Introductionmentioning
confidence: 99%